Coated chitosan pellets containing rutin intended for the treatment of inflammatory bowel disease: in vitro characteristics and in vivo evaluation - Rabišková, Miloslava; Bautzová, Tereza; Gajdziok, Jan; Dvořáčková, Kateřina; Lamprecht, Alf; Pellequer, Yann; Spilková, Jiřina (International journal of pharmaceutics, 2012)
Preparation of coated pellets intended for rutin colon delivery, their evaluation in vitro and in vivo in experimental colitis in rats was the purpose of this study. Pellets were obtained using extrusion/spheronization and coated with three types of coatings (caffeic acid/hypromellose/alginic acid; sodium alginate/hypromellose/zinc acetate; sodium alginate/chitosan). Dissolution using buffers of pH values, β-glucosidase and times corresponding to gastrointestinal tract (GIT) was provided. Pellets coated with alginate/chitosan showed low rutin dissolution (12-14%) in upper GIT conditions and fast release (87-89%) under colon conditions; that is a good presumption of intended rutin release. After colitis induction and development, the rats were treated with pellets and rutin solution administered orally, solution also rectally. Colon/body weight ratio, myeloperoxidase activity and histological evaluation were performed. Rutin was able to promote colonic healing at the dose of 10mg/kg: colon/body weight ratio decreased and myeloperoxidase activity was significantly suppressed. Pellets coated with alginate/chitosan applied orally and rutin solution administered rectally showed the best efficacy. The combination of rutin as natural product, mucoadhesive chitosan degraded in the colon and sodium alginate as the main coating substance in the form of pellets create a promising preparation for therapy of this severe illness.
Keywords: Hypromellose Derivatives; kyseliny hexuronové; algináty; farmaceutická chemie; kolon; Chitosan; pufry; Drug Stability; Trinitrobenzenesulfonic Acid; antiflogistika; rutin; Methylcellulose; methylcelulosa; Gastrointestinal Agents; Rutin; implantované léky; rozpustnost; krysa rodu Rattus; Administration, Oral; Colon; deriváty hypromelózy; zvířata; Alginates; potkani Wistar; časové faktory; kyseliny kávové; Buffers; Hexuronic Acids; Rats, Wistar; Male; Drug Implants; Technology, Pharmaceutical; octan zinečnatý; Drug Compounding; Hydrogen-Ion Concentration; Solubility; Zinc Acetate; příprava léků; kyselina glukuronová; stabilita léku; Glucuronic Acid; Chemistry, Pharmaceutical; kyselina trinitrobenzensulfonová; Anti-Inflammatory Agents; Rats; kolitida; aplikace orální; gastrointestinální látky; farmaceutická technologie; Animals; mužské pohlaví; koncentrace vodíkových iontů; chitosan; Disease Models, Animal; Time Factors; Caffeic Acids; Colitis; modely nemocí na zvířatech